2015
DOI: 10.1007/s10620-015-3941-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Aspiration Pneumonia After Endoscopic Hemostasis

Abstract: Specific risk factors for aspiration pneumonia after endoscopic hemostasis were identified. Endoscopists should carefully consider aspiration pneumonia when managing older patients who are on hemodialysis, have a history of stroke, and undergo a longer procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Another mechanism leading to the development of postoperative pneumonia is aspiration in endoscopic hemostasis, as outlined in a retrospective study of 504 patients by Kawanishi et al [17]. They reported a postoperative aspiration pneumonia incidence of 4.8%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism leading to the development of postoperative pneumonia is aspiration in endoscopic hemostasis, as outlined in a retrospective study of 504 patients by Kawanishi et al [17]. They reported a postoperative aspiration pneumonia incidence of 4.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the model for end-stage liver disease (MELD) score was higher in VAP patients on univariate analysis. Kawanishi et al [17] identified age >75 years (OR: 4.4; 95% CI: 1.5 - 13.6; P = 0.0073), procedural duration > 30 min (OR: 5.6; 95% CI: 1.9 - 18.2; P = 0.0023), hemodialysis (OR: 3.6; 95% CI: 1.2 - 11; P = 0.024), and a history of stroke (OR: 3.8; 95% CI: 1 - 14; P = 0.041) as independent risk factors for developing postoperative pneumonia. Okamura et al [20] identified higher lung age (OR: 1.02; 95% CI: 1.00 - 1.03; P = 0.010) and lower body mass index (OR: 0.89; 95% CI: 0.82 - 0.96; P = 0.006) as independent risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…2). [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Most of the identified instances were in adult patients who had substantial underlying illness, with propofol as the principal sedative. The eight deaths resulted from procedures performed for percutaneous endoscopic gastrostomy tube placement (n¼4), active gastrointestinal bleeding (n¼3), or endoscopic submucosal dissection (n¼1).…”
Section: Resultsmentioning
confidence: 99%
“…• Barbara and colleagues 2015: 30 A 50-yr-old ICU patient aspirated during fentanyl and midazolam facilitated endoscopy for active GI bleeding and suffered cardiac arrest; despite resuscitation he died shortly thereafter of multi-organ failure. • Kawanishi and colleagues 2016: 31 24 adults aspirated during diazepam-facilitated endoscopy for active GI bleeding; 3 were intubated and 1 died. • Park and colleagues 2013: 32 38 adults aspirated during propofol or midazolam-facilitated endoscopic submucosal dissection; 1 death.…”
Section: Reports Including Deaths Resulting From Aspirationmentioning
confidence: 99%
“…p value < 0.05 was considered statistically significant and odds ratios (ORs) with 95% confidence intervals (CIs) were determined. Data were statistically analyzed using JMP version 9 software (SAS Institute, Cary, NC, USA) [15]. …”
Section: Methodsmentioning
confidence: 99%